1999
DOI: 10.1097/00000658-199901000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Laparoscopy-Assisted Billroth I Gastrectomy

Abstract: Quality of life after Billroth I gastrectomy was significantly better in patients in whom a laparoscopic technique was used than in those who underwent a conventional method. LAG is less invasive and better accepted by patients and is the procedure of choice for the treatment of early gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
176
2
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(186 citation statements)
references
References 17 publications
1
176
2
6
Order By: Relevance
“…There have been studies that investigated QoL after LADG. Adachi et al [8] assessed the QoL in patients following LADG and ODSG, using their own questionnaire comprised of 24 questions, with a mean follow-up period of 24 months. That study demonstrated better QoL in patients after LADG regarding weight loss, swallowing difficulty, heartburn and belching, early dumping syndrome, and total score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies that investigated QoL after LADG. Adachi et al [8] assessed the QoL in patients following LADG and ODSG, using their own questionnaire comprised of 24 questions, with a mean follow-up period of 24 months. That study demonstrated better QoL in patients after LADG regarding weight loss, swallowing difficulty, heartburn and belching, early dumping syndrome, and total score.…”
Section: Discussionmentioning
confidence: 99%
“…The early postoperative quality of life (QoL) following LADG has been shown to be superior to that following ODSG [8,9]. However, there have been some doubts about the long-term QoL benefits from LADG [10], and Yasuda et al [11] showed that the long-term QoL of patients was similar for LADG and ODSG.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported early results of LADG's safety and short-term benefits [5][6][7]. In 2015, the long-term results of the KLASS trial will be reported.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan and Korea, the superiority of laparoscopyassisted gastrectomy (LAG) for early gastric cancer compared with conventional open gastrectomy has been confirmed by both randomized and nonrandomized clinical studies, with advantages including less intraoperative bleeding, less pain, and shorter postoperative hospital stays [4][5][6][7][8][9][10][11][12]. Reported postoperative complication rates are comparable between LAG and conventional open gastrectomy cases.…”
Section: Introductionmentioning
confidence: 99%